2022
DOI: 10.3390/cancers14174240
|View full text |Cite
|
Sign up to set email alerts
|

The Nitric Oxide Donor [Zn(PipNONO)Cl] Exhibits Antitumor Activity through Inhibition of Epithelial and Endothelial Mesenchymal Transitions

Abstract: Exogenous nitric oxide appears a promising therapeutic approach to control cancer progression. Previously, a nickel-based nonoate, [Ni(SalPipNONO)], inhibited lung cancer cells, along with impairment of angiogenesis. The Zn(II) containing derivatives [Zn(PipNONO)Cl] exhibited a protective effect on vascular endothelium. Here, we have evaluated the antitumor properties of [Zn(PipNONO)Cl] in human lung cancer (A549) and melanoma (A375) cells. Metastasis initiates with the epithelial–mesenchymal transition (EMT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…One example is the inhibition of melanoma cell growth observed upon scavenging endogenous NO, which was restored by using a NO donor [10]. However, NO-induced melanoma apoptosis and its mechanism is not clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“…One example is the inhibition of melanoma cell growth observed upon scavenging endogenous NO, which was restored by using a NO donor [10]. However, NO-induced melanoma apoptosis and its mechanism is not clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Inducible NOS (iNOS) and NO downregulation promoted EMT and metastasis in colorectal cancer [ 20 ]. An NO donor exhibited antitumour activity through inhibition of EMT in human lung cancer and melanoma cells [ 21 ]. Increased reactive oxygen species (ROS) levels lead to the development of fibrosis by inducing oxidative damage during EMT in the lens.…”
Section: Discussionmentioning
confidence: 99%
“…In lens fibrosis, L-arginine metabolism is altered by the expression and activity of ARG1, which ultimately affects collagen synthesis. Exogenous NO may retard the development of fibrosis by preventing oxidative damage-induced EMT [ 20 , 21 ]. Arginase activation leads to decreased NO bioavailability, increased superoxide levels, and decreased antifibrotic effects [ 22 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells co-cultured with lung cancer cells were shown to acquire a mesenchymal phenotype with increased vimentin, alpha smooth muscle actin and Smad2/3, and reduced VE-cadherin. These changes were prevented in the presence of [Zn(PipNONO)Cl], suggesting [Zn(PipNONO)Cl] as a promising therapeutic tool to control tumor growth and metastasis [ 146 ]. In another study, alpha-1 antitrypsin was shown to induce EndMT in lung cancer cells, suggesting alpha-1 antitrypsin as a factor associated with tumor metastasis in lung carcinoma [ 147 ].…”
Section: Extravasation Of Tumor Cells Through the Blood–brain Barrier...mentioning
confidence: 99%